2017
DOI: 10.3892/ol.2017.7629
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node retrieval after dissolution of surrounding adipose tissue for pathological examination of colorectal cancer

Abstract: Abstract. Examination of >12 lymph nodes (LNs) is important for the diagnostic accuracy of nodal status following resection of colorectal cancer. In the present study, the efficacy of a fat dissolution technique for LN retrieval was evaluated using resected colon and rectum mesentery. First, the resected mesentery was searched for LNs by inspection and palpation immediately after surgery. Subsequently, fat dissolution liquid was applied to the remnant fat and the LN search was repeated. The primary endpoint wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Data from Kochi Mecical School hospital suggest that with the conventional manual method, a mean of 14 lymph nodes is retrieved, and data from a preliminary study suggested that fat-dissolution method yielded an additional seven lymph nodes 5) . Thus, the sample size for the proposed trial was calculated based on the hypothesis that the fat-dissolution liquid could increase the mean number of lymph nodes retrieved from 14 to 21, with a standard deviation of 7.4.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…Data from Kochi Mecical School hospital suggest that with the conventional manual method, a mean of 14 lymph nodes is retrieved, and data from a preliminary study suggested that fat-dissolution method yielded an additional seven lymph nodes 5) . Thus, the sample size for the proposed trial was calculated based on the hypothesis that the fat-dissolution liquid could increase the mean number of lymph nodes retrieved from 14 to 21, with a standard deviation of 7.4.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…3 Methylene blue staining, modified Davidson's fixation, or fat dissolution enables to detect more small lymph nodes and micrometastases in the resected colon and mesentery. [17][18][19] In addition, the number of lymph nodes may vary from person to person. Interestingly, as in this paper, Asian race/ Pacific Island descent (presumably less obese than other races), younger age, higher stage of colon cancer, and right-side colon cancer had more compliance with ''12 RLN,'' which may reflect the fact that more lymph nodes are harbored in the mesentery of these certain populations.…”
mentioning
confidence: 99%